(untitled) - Park, Sung-Jo (New York, 2003)
This book examines the need for cooperation between Europe and Asia, particularly in view of China's accession to the WTO. It looks at the cultural implications for closer cooperation between the two parts of the world, exploring corporate culture and leadership in integration management through mergers and acquisitions. It then goes onto discuss whether the world is big enough for several cultures or whether further integration will result in homogenization.
Keywords: Industrial management,Industrial management,Intercultural communication,Intercultural communication,International trade,Competition, international,Asia; Congresses,Congresses,Congresses,Congresses,Congresses,Congresses,Foreign economic relations,Congresses; Asia,Europe,Asia,Europe,Europe